Morphometric analysis of the maxillary root apex positions according to crowding severity. (30th August 2017) - Kim, S. H.; Shin, S. M.; Choi, Y. S.; Ko, C. C.; Kim, S. S.; Park, S. B.; Son, W. S.; Kim, Y.‐I.
Structured Abstract: Objectives: To determine differences in arch forms derived from the root apices locations between individuals with <2 mm maxillary crowding and controls. Setting and Sample Population: The Department of Orthodontics, Pusan National University. Cone‐beam computed tomography (CBCT) images of 102 patients in the control group and 95 patients in the crowding group. Materials and Methods: X, Y and Z coordinates of the tip of the crowns and the apex of the root of the maxillary teeth (except second molars) were determined on the CBCT images. The acquired three‐dimensional (3D) coordinates were converted into two‐dimensional (2D) coordinates via projection on the palatal plane, and the Procrustes analysis was employed to process the converted 2D coordinates. The mean shape of the arch form derived from the location of the tip of the crowns and the apex of the root was compared between groups using the statistical shape analysis. Results: There was a statistically significant difference ( P  = .046) between the groups for the mean shape of the root apex arch form, but the difference was small and clinically irrelevant as it is minor compared to the degree of crowding. Conclusions: Maxillary arch from at the level of the maxillary apices only shows minor differences between crowded and non‐crowded dentitions.